Peran Faktor Demografi Dan Karakteristik Sosial Terhadap Kesediaan Menjalani Tes HIV Pada Perempuan Usia Reproduksi - Flora Honey Darmawan; Hadayana Sukandar; Farid Husin (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: The incidence of HIV and AIDS among women shows a significant increase, 90 % of which is infected by her sexual partner. HIV-infected status can only be detected by undergoing HIV tests; one of them is through mobile VCT services. In fact, there are women of reproductive age who are not willing to undergo HIV testing. Objective: The purpose of this study is to analyze the role of demographic factor and social characteristics towards the willingness to undergo HIV testing among women of reproductive age in the city of Bandung. Method: Research methods are case control with sampling by consecutive sampling. Research is done in 7 subdistricts in the city of Bandung during May to July 2013. The sample reaches 90 women of reproductive age following mobile VCT, 45 respondents are not willing to undergo HIV testing (case group) and 45 of whom are willing to undergo HIV testing (control group). Data collected through questionnaires are then analyzed with chi square and multiple logistic regressions. Result: The results show that demographic factors i.e. age <20 or ≥35 years, lack of education, unemployment, and unmarried status, are not responsible in the willingness to undergo HIV testing (p>0,05). Social characteristics include lack of knowledge, the perception that she is not at risk, high stigma, and lack of certainty in VCT services. These influence the willingness to undergo HIV test (p<0,05). Based on multivariable analysis, the perception that she is not at risk is the most dominant factor in the willingness to undergo HIV testing with OR = 5,916 (CI95%: 1,563 to 22,393). PAR analysis shows that 80% proportion of women who are not willing to undergo HIV testing can be prevented by eliminating the perception that she is not at risk of contracting HIV or increasing the perception that she is at risk. Conclusion: Research conclusion state that demographic factor has no role in the willingness to undergo HIV testing, in the contrary, social characteristics contribute the willingness to undergo HIV testing among women of reproductive age. The perception that she is not at risk is the most substantial factor in the willingness to undergo HIV testing among women of reproductive age in Bandung. Keywords: demographic factors, social characteristics, the willingness of HIV testing, mobile VCT